2011
DOI: 10.1164/rccm.201002-0188oc
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Tyrosine Kinase Inhibition Worsens Acute Lung Injury in Mice with Repairing Airway Epithelium

Abstract: EGFR inhibition in repairing airway epithelial cells modulated significant expression of genes involved in the airway microenvironment, prolonged inflammation, and potentiated acute lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 30 publications
5
67
0
1
Order By: Relevance
“…The importance of EGFR activation in naphthalene-induced lung injury was recently explored using the EGFR tyrosine kinase inhibitor gefitinib (24). The results suggested that EGFR inhibition prolongs lung injuries associated with increased neutrophil sequestration, especially at earlier stages of epithelial regeneration (24,29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The importance of EGFR activation in naphthalene-induced lung injury was recently explored using the EGFR tyrosine kinase inhibitor gefitinib (24). The results suggested that EGFR inhibition prolongs lung injuries associated with increased neutrophil sequestration, especially at earlier stages of epithelial regeneration (24,29).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that EGFR inhibition prolongs lung injuries associated with increased neutrophil sequestration, especially at earlier stages of epithelial regeneration (24,29). Although neutrophil infiltration is commonly associated with acute lung injury, neutrophils are also capable of promoting epithelial repair mechanisms (55).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of them are mitogens in type II pneumocytes, and act synergistically to mediate their maturation and increase surfactant synthesis [8]. EGF had benefi cial eff ects in an animal model of ALI [39], and inhibition of EGF receptor had a detrimental eff ect during airway epithelium repair [40]. KGF has been linked to upregulation of anti-infl am matory cytokines and modulation of epithelial cell migration [41].…”
Section: Therapeutic Strategies Aimed At Lung Repairmentioning
confidence: 99%